Role of NGOs in Microfinancing through Self Help Groups-A Study in Kanyakumari District - Stephen, J. K.; Seilan, A. (Indian Journal of Marketing, 2005)
Development interventions in the rural areas by Voluntary Agencies (VAs) or, as they came to be known later, on Government Organization (NGOs) dates back to the pre- independence days. These interventions emanated from the prevailing situation of mass poverty, due to high levels of illiteracy and social discrimination as well as the inability of the official delivery mechanism to reach the benefits of social and economic development to the weaker sections of the rural society in their economic pursuits. The inability of credit institutions to cover a sizeable segment of the rural poor is generally attributed to the high cost of administering large number of small loans and the perceived lending risks in the absence of any collateral. This promoted a number of VAs/NGOs to enter the rural credit scene for organizing the poor into informal groups for mutual help and benefit many of these groups have been provided credit support. These NGOs are instrumental in promoting informal structures of the poor to help them save and promote self-reliance in financing their needs through the concept of self-help groups. (SHGs).